Clinical Utility of the Addition of Molecular Genetic Testing to Newborn Screening for Sickle Cell Anemia - Shook, Lisa M.; Haygood, Deidra; Quinn, Charles T. (Frontiers in Medicine, 2021)
Sickle cell disease (SCD) is a group of related yet genetically complex hemoglobinopathies. Universal newborn screening (NBS) for SCD is performed in the United States and many other nations. Classical, protein-based laboratory methods are often adequate for the diagnosis of SCD but have specific limitations in the context of NBS. A particular challenge is the differentiation of sickle cell anemia (SCA) from the benign condition, compound heterozygosity for HbS and gene-deletion hereditary persistence of fetal hemoglobin (HbS/HPFH). We describe a sequential cohort of 44 newborns identified over 4.5 years who had molecular genetic testing incorporated into NBS for presumed SCA (an “FS” pattern). The final diagnosis was something other than SCA in six newborns (12%). Three (7%) had HbS/HPFH. All had a final, correct diagnosis at the time of their first scheduled clinic visit in our center (median 8 weeks of age). None received initial counseling for an incorrect diagnosis. In summary, genetic testing as a component of NBS for SCD is necessary to provide correct genetic counseling and education for all newborns' families at their first visit to a sickle cell center. Genetic testing also permits the use of early, pre-symptomatic hydroxyurea therapy by preventing infants with HbS/HPFH from receiving unnecessary therapy. We argue that genetic testing should be incorporated into contemporary NBS for SCD.